Haematological and genotoxic profile study of workers exposed to medical waste - Alex Veras Pereira; Filiphe Daniel Luz Martins Rocha; Ananda do Nascimento Oliveira; Fabricio Ibiapina Tapety; Ana Amélia de Carvalho Melo Cavalcante; Tatiana Vieira Souza Chaves (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To evaluate the haematological and genotoxic profile of workers exposed to medical waste. Method: Descriptive study of an observational nature, performed with two distinct groups: exposed (20 individuals) and unexposed (20 individuals), which had blood samples collected for analysis. Results: The results revealed an increased erythrocytes, hematocrit and leukocytes of the exposed group compared to the unexposed group. In the group exposed were identified: eosinophilia (45%), atypical lymphocytes (35%) and neutrophil toxic granulation (25%). It revealed a significant genotoxic effect by the content and frequency of major damage in the exposed group. There was no correlation of these results with the habits and life styles reported. Conclusion: It was found that the study group might be undergoing reaction processes caused by some agent, as well as genetic instability. These data highlight the need for greater biomonitoring of these workers in order to prevent neoplastic conditions. Descriptors: Medical Waste, Waste Collectors, Occupational Risk.